Rancang Bangun Keamanan Rumah Berbasis IOT Dengan Sensor Pir Dan Kamera IOT - Viktorius Ando Saputra; Genrawan Hoendarto; Ricky I. Ndaumanu (LPPM Universitas Widya Dharma Pontianak, 2025)
The rising threat of crimes, such as theft, necessitates a home security system capable of delivering rapid and accurate alerts. This research aims to develop an integrated and responsive Internet of Things (IoT)-based home security system. The method used involves designing a prototype that utilizes an ESP32-CAM module as the central controller, supported by a Passive Infrared (PIR) sensor for motion detection and an MC-38 magnetic sensor for door access detection. The research results show that the developed system successfully integrates all components. When a sensor detects suspicious activity, the system is capable of automatically capturing visual evidence and sending real-time notifications to the homeowner's mobile device via a WiFi network. In conclusion, this system offers a practical, efficient, and affordable security solution. The integration of multiple sensors with real-time visual notifications is proven to enhance vigilance and provide better protection against potential threats in residential environments.